Emerging Roles of Vascular Endothelium in Metabolic Homeostasis. Issue 4 (3rd August 2018) - Pi, Xinchun; Xie, Liang; Patterson, Cam
Abstract : Our understanding of the role of the vascular endothelium has evolved over the past 2 decades, with the recognition that it is a dynamically regulated organ and that it plays a nodal role in a variety of physiological and pathological processes. Endothelial cells (ECs) are not only a barrier between the circulation and peripheral tissues, but also actively regulate vascular tone, blood flow, and platelet function. Dysregulation of ECs contributes to pathological conditions such as vascular inflammation, atherosclerosis, hypertension, cardiomyopathy, retinopathy, neuropathy, and cancer. The close anatomic relationship between vascular endothelium and highly vascularized metabolic organs/tissues suggests that the crosstalk between ECs and these organs is vital for both vascular and metabolic homeostasis. Numerous reports support that hyperlipidemia, hyperglycemia, and other metabolic stresses result in endothelial dysfunction and vascular complications. However, how ECs may regulate metabolic homeostasis remains poorly understood. Emerging data suggest that the vascular endothelium plays an unexpected role in the regulation of metabolic homeostasis and that endothelial dysregulation directly contributes to the development of metabolic disorders. Here, we review recent studies about the pivotal role of ECs in glucose and lipid homeostasis. In particular, we introduce the concept that the endothelium adjusts its barrier function to control the transendothelial transport of fatty acids, lipoproteins, LPLs (lipoprotein lipases), glucose, and insulin. In addition, we summarize reports that ECs communicate with metabolic cells through EC-secreted factors and we discuss how endothelial dysregulation contributes directly to the development of obesity, insulin resistance, dyslipidemia, diabetes mellitus, cognitive defects, and fatty liver disease.